Water-promoted diels-alder reaction in quaternary ammonium salts - Nagare, Amit S.; Manna, Arpan; Sonawane, Pramod D.; Kumar, Anil (Journal of Physical Organic Chemistry, 2015)
{Prevailing classification of salts based on their effect in solubility and stability of proteins in aqueous solution predicts that tetraalkylammonium salts, guanidinium chloride (GnCl), LiClO4 act as salting-in (S/I) and LiCl, NaCl act as salting-out (S/O) in aqueous conditions. In the same context the behaviour of GnCl, LiClO4 and LiCl are contradictory in polar solvents like ethylene glycol and formamide. In these solvents, expected salt effect shows just opposite nature from their usual expectation. However, in the aqueous solution salts like tetraalkylammonium halide (R4NX
Keywords: Delta G(solvation); Diels-Alder reaction; k(s); kinetic study; solubility; tetraalkylammonium salts; viscosity